The Alchemy of Exile: Strengthening a Culture of Human Rights in the Burundian Refugee Camps in Tanzania - Jennifer Moore (Washington University Journal of Law & Policy, 2008)
This Essay explores the ways in which human rights norms can be internalized and redefined from within a community of refugees, in this case Burundians residing in camps in Western Tanzania. It examines the everyday relevance of international protection principles to a particular group of individuals those norms are intended to serve.
Keywords: Emigration & immigration -- Government policy; Refugees -- Tanzania; Burundians; Human rights; Immigration policy; Refugees; United Nations Convention Relating to the Status of Refugees; Burundi; Tanzania; United States